CUTTING TOOL WEAR CONTROL IN AUTOMATIC CONTROL PROCESS OF DRILLING - J.A. MARKARIAN (Advanced Engineering Research)
According to the results of experimental research the wear of drill and the corresponding changes of vibroacoustic signal intensity in the cutting zone and the consuming power of spindle rotation engine at the fixed supply of forth are considered.